Frozen Sections of Sentinel Lymph Nodes From Breast Cancer Patients Who Undergo Neoadjuvant Therapy Are Accurately Diagnosed Using Telepathology. (11th September 2019) - McMurtry, Valarie; Factor, Rachel
Abstract: Objectives: Telepathology enables histologic diagnosis to be made from a scanned slide visualized on a computer. Frozen sections (FSs) can be performed at remote locations and read by a pathologist at a central site. At our institution, qualifying breast cancer patients are enrolled in clinical trials that require FS on sentinel lymph nodes (SLNs) after neoadjuvant therapy (NAT), including chemotherapy or endocrine therapy. In this setting, histology is complicated by treatment effect and biopsy site changes. Others have reported good accuracy of FSs on SLNs after NAT. We investigated whether pathologists are accurate in diagnosing SLN FSs for such cases while using telepathology. To our knowledge, this has not been reported previously. Methods: SLNs were entirely submitted and serially sectioned (2-mm thickness). At least two levels were cut. All FSs were submitted for formalin-fixed, paraffin-embedded permanent sections. A pathology assistant at the remote location prepared the FSs and scanned slides using the VisionTek M6 digital microscope ecosystem (East Dundee, IL). Cases were interpreted by board-certified pathologists who completed training on the VisionTek system. For this study, diagnoses from FSs and permanents were compared. Results: Forty-five SLNs from 19 breast neoadjuvant cases were read by VisionTek from March 2017 to January 2019. Forty-three cases (96%) called negative by FSs were confirmed negative (on permanents). One hundred percent called positive by FSs were positive. Four SLN called atypical on FSs were positive. Three of these were neoadjuvant endocrine cases for invasive lobular carcinoma. Two cases called atypical were negative. One of these, called atypical/suspicious, resulted in axillary dissection. This case was reviewed by three pathologists at the time of surgery. It had abundant treatment effect, mimicking carcinoma. Conclusion: While pitfalls exist, overall, the diagnostic accuracy of frozen section analysis by telepathology of SLNs from breast cases after neoadjuvant therapy is high.